THE EXPRESSION OF THE INTERLOCUTOR’S IMAGE BASED ON THE PRINCIPLE OF POLITENESS - Tursunova Parvina Mamurjonovna (Modern American Journals, 2025)
This article presents a linguopragmatic analysis of the formation of the interlocutor’s image based on the principle of politeness in Spanish. The study uses examples of both formal and informal communication to demonstrate the influence of the interlocutor’s social status, age, and gender, as well as social distance and communicative context, on politeness strategies. It examines how lexical units, grammatical constructions, discourse markers, phonetic devices, and pragmatic mitigators contribute to the expression of the interlocutor’s image. The results show that positive and negative politeness strategies in Spanish communicative culture have distinct pragmatic features.
Keywords: Principle of politeness, interlocutor’s image, Spanish language, tú–usted opposition, pragmatic mitigators, linguopragmatics.